Isolating the role of time in bed restriction in the treatment of insomnia: a randomised, controlled, dismantling trial comparing sleep restriction therapy with time in bed regularisation - Maurer, LF; Espie, CA; Omlin, X; Reid, MJ; Sharman, R; Gavriloff, D; Emsley, R; Kyle, SD (Oxford University Press, 2020)
Study Objectives Sleep restriction therapy (SRT) is one of the most effective treatments for insomnia. Restriction of time in bed (TIB) is assumed to be the central mechanism through which SRT improves sleep consolidation and reduces insomnia symptoms. This hypothesis has never been directly tested. We designed a randomised, controlled, dismantling trial in order to isolate the role of TIB restriction in driving both clinical and polysomnographic sleep outcomes.